2008
DOI: 10.1143/jjap.47.6413
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Diffusion Tracing in Li Ionic Conductors by the Short-Lived Radioactive Beam of 8Li

Abstract: A non-destructive and on-line diffusion tracing in Li ionic conductors has been demonstrated. As the tracer, the pulsed beam of the short-lived -emitting radioisotope of 8 Li was implanted into a typical Li ionic conductor LiGa. By analyzing the timedependent yields of the -particles measured in coincident with the repetition cycle of the beam, the tracer diffusion coefficients were extracted with a good accuracy. The ordering of the Li vacancies in the Li-deficient phase of LiGa was observed for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Consequently, in literature only some special publications can be found. There are experiments based on the radio tracer method using the prompt alpha-decay following the beta-decay of the short-lived isotope 8 Li (t 1/2 = 0.84 s) [17]. Such elegant experiments are, however, of low significance for slow diffusivities due to the limited annealing time period available.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, in literature only some special publications can be found. There are experiments based on the radio tracer method using the prompt alpha-decay following the beta-decay of the short-lived isotope 8 Li (t 1/2 = 0.84 s) [17]. Such elegant experiments are, however, of low significance for slow diffusivities due to the limited annealing time period available.…”
Section: Introductionmentioning
confidence: 99%
“…In the present case, however, the inherent energy distribution of the a particles is continuous and broad [7]. Although the correspondence between the emitted position and measured energy of the charged particles is not as simple as above-mentioned, it was shown that the tracer diffusion coefficient could be obtained from the time-dependent yields of a particles emitted by diffusing 8 Li with the help of the simulation [8][9][10]. Fig.…”
Section: Measurement Of LI Diffusion Length From Micrometer To Nanomementioning
confidence: 61%
“…400 keV in Ref. [9]) were traced with time, allowing to measure diffusion coefficients in Li ionic conductors with an accuracy of about 20% and sensitivity down to 10 À10 cm 2 /s [9]. However, no diffusion effects were observed when applying the method for measuring lithium diffusion coefficients in LiCoO 2 even at the temperature of 573 K (maximum temperature accessible in the experimental set-up used so far, see Fig.…”
Section: Measurement Of LI Diffusion Length From Micrometer To Nanomementioning
confidence: 99%
See 2 more Smart Citations